Mental Health Transformation in the Generation Z Era: Mentoring and Prevention of Early Marriage in Adolescents: Transformasi Kesehatan Mental Era Generasi Z: Pendampingan dan Pencegahan Pernikahan Dini pada Remaja - Sartika, Andry; Rozani, Leni; Ferasinta, Ferasinta; Novitasari, Selvia (KHD Production, 2025)
Early marriage is one of the social problems in Indonesia both in rural and urban areas that is very serious and must be a concern from various parties because of the various risks that may occur. There are 16 million births that occur in mothers at the age of 15-19 years Women between the ages of 10-14 years have a fairly high-risk level, which is 5 times the risk of dying during pregnancy or childbirth. Indonesia ranks 37th in the world in terms of early marriage and ranks 2nd in ASEAN. Community service activities in the form of health counseling to adolescents are carried out using the lecture method and also distributing leaflets to each student. Counseling activities related to the topic and lecture method used can continue to be carried out to be able to increase the understanding and knowledge of adolescents related to the impact of marriage carried out at an early age. The results of the counseling showed an increase in students' understanding of the disease of early marriage, including the impacts and consequences it causes. The enthusiasm from the school and students was very good. Suggestions were given so that the school better controls and assists students to prevent underestimation of the disease, and students are expected to be more socially friendly and sensitive to the environment.